AN ANALYSIS OF PERSUASIVE LANGUAGE USED IN WRISTWATCH ADVERTISEMENT AT TIME MAGAZINE - KURNIAWATI , EKO PUJI (2007)
This observation has purposes to know the ways of persuasion language expressed in wristwatch advertisement in Time Magazine and to describe the meaning of persuasive language used in wristwatch advertisement in Time Magazine. In this research, the data are derived from the English text in wristwatch advertisement that containing word, phrase, clause or sentence. There are two techniques in collecting the data, firstly the writer reads the English advertisement in Time Magazine especially the wristwatch advertisement; secondly the writer lists and collects phrases or sentence of the wristwatch advertisement in Time Magazine. And then the writer uses persuasive technique in language to get the ways persuasive language expressed and using contextual meaning to know the meaning of persuasive language. Based on the data analysis, the writer draws conclusion that there are eight ways to express persuasive language in wristwatch advertisement at Time magazine. They are intensifier, imperative, rhetorical question, repetition, simile, metaphor, short cut, and temporal language. And then related to the meaning, the meaning used to express persuasive presents by using superiority of wristwatch, prestige of wristwatch, the quality of wristwatch and the freedom of wearer to set the wristwatch as their want.